Gestión municipal y desempeño laboral en la Municipalidad Provincial de Maynas, 2022 - Vela Rengifo, Anabel (2023)
For the present study, the objective was to specify the existence of a relationship between municipal management and labor performance in the municipality of the district of Maynas, 2022. Likewise, it was indicated if the first variable influences the second variable. The type of research is basic-non-experimental, of a cross-sectional design, and the sample was made up of 99 workers from the municipality. According to the results, it has been determined that with an observed critical value of 0.000<0.05; if there is a significant relationship between both study variables, for which reason it is argued that in a certain way variable 1 has a degree of influence on the decisions of variable 2.